Treewidth, Pathwidth and Cospan Decompositions - Blume, Christoph; Bruggink, H. J. Sander; Friedrich, Martin; König, Barbara (Electronic Communications of the EASST, 2011)
We will revisit the categorical notion of cospan decompositions of graphs and compare it to the well-known notions of path decomposition and tree decomposition from graph theory. More specifically, we will define several types of cospan decompositions with appropriate width measures and show that these width measures coincide with pathwidth and treewidth. Such graph decompositions of small width are used to efficiently decide graph properties, for instance via graph automata.